Reviews. Issue 1 (1st October 2015) - Hennigan, Keith; Kamp, Michiel
A Composer's Guide to Game Music, Winifred Phillips (2014) Cambridge, MA: MIT Press, 288 pp., ISBN: 9780262026642, h/bk, £20.95Sound Play, William Cheng (2014) Oxford and New York: Oxford University Press, 240 pp., ISBN: 9780199969968, h/bk, £65.00 ISBN: 9780199969975, p/bk, £16.99